Analyzing the Professional competencies of qur'an and hadith teachers in the digital era and society 5.0: A library research - Lilik Anirowati; Irjus Indrawan; Asmariani Asmariani (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the professional competencies of Qur'an and Hadith teachers and to identify the challenges and development strategies associated with these competencies within the context of contemporary Islamic education. The research employed a library research method using a descriptive qualitative approach. Data were collected from books, scholarly journal articles, policy documents, and previous studies relevant to teacher professional competence, Islamic education, and Qur'an and Hadith instruction. The data were analyzed using content analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the professional competence of Qur'an and Hadith teachers encompasses mastery of Qur'anic and Hadith knowledge, the ability to develop instructional materials, digital competence, and the capacity for continuous professional development. Furthermore, Qur'an and Hadith teachers face various challenges, including rapid technological advancements, changing student characteristics, and the increasing complexity of contemporary religious issues. Therefore, strengthening professional competence should be pursued through continuous education and training, the enhancement of digital literacy, the development of professional learning communities, and the promotion of research and reflective practices. Consequently, the professional competence of Qur'an and Hadith teachers serves as a strategic factor in improving the quality of learning and supporting the realization of adaptive, high-quality, and relevant Islamic education in response to contemporary societal developments.